Effect of laser irradiation on bond strength between zirconia and resin cement or veneer ceramic: A systematic review and meta-analysis - Bitencourt, Sandro [UNESP]; Ferreira, Leti´cia [UNESP]; Mazza, Leticia [UNESP]; Dos Santos, Daniela [UNESP]; Pesqueira, Aldieris [UNESP]; Theodoro, Leticia [UNESP] (Wolters Kluwer, 2021)
Aim: This systematic review with meta-analysis aimed to evaluate the effect of the laser treatment on bond strength between Y-TZP and the resin cement or with the veneering ceramic, and the effect on the alteration of the Y-TZP surface roughness. Settings and Design: Systematic review and meta analysis following PROSPERO guidelines. Materials and Methods: A comprehensive review was performed up to September 2020 on four databases (PubMed/MEDLINE, Embase, Scopus, and Cochrane Library), using the combination of keywords: 'laser AND zirconia AND surface treatment AND bond strength'. Statistical Analysis Used: The meta-analysis was based on the Mantel-Haenszel and inverse variance methods. The continuous outcome was evaluated by mean difference and the corresponding 95% confidence intervals. Results: A total of 37 studies were identified for the inclusion of data, with only in vitro studies. The types of laser reported in the studies were: Er:YAG, Nd:YAG, Er,Cr:YSGG, CO2, Femtosecond, and Yb lasers. A random-effect model found statistically significant differences between lasers and control groups of Y-TZP (P < 0.00001; MD: 3.08; 95% CI: 2.58 to 3.58). Only the bond strength with the Er:YAG laser did not present statistical difference (P = 0.51; MD: 0.22; 95% CI:-0.44-0.88). In another analysis, a random-effect model found a statistically significant difference between the laser and control groups on surface roughness (P < 0.00001; MD: 0.96; 95% CI: 0.86 to 1.06). Conclusions: Laser irradiation is capable to improve the Y-TZP surface roughness and the bond strength of zirconia with resin cement and veneering ceramics. However, there is a lack of laser protocol for the zirconia surface, a fact that makes a simple and direct comparison difficult.
Keywords: Lasers; resin cement; shear strength; veneering ceramic; zirconium oxide